High prevalence of multidrug-resistant gram-negative bacterial infection following pediatric liver transplantation. Issue 45 (6th November 2020) - Phichaphop, Chanita; Apiwattanakul, Nopporn; Techasaensiri, Chonnamet; Lertudomphonwanit, Chatmanee; Treepongkaruna, Suporn; Thirapattaraphan, Chollasak; Boonsathorn, Sophida
Abstract : Abstract: Bacterial infection has been identified as one of the most significant complications of liver transplantation (LT). Multidrug-resistant (MDR) gram-negative bacteria (GNB) infection remains problematic issue following LT in the adults. However, data in children are scarce. We aimed to examine the prevalence and associated factors of MDR-GNB infection among pediatric LT recipients. We performed a single-center retrospectively study of 118 children who underwent LT between January 2010 and December 2018. Data on the prevalence, clinical characteristics, types, and sites of MDR-GNB infection within 3 months after LT as well as the treatment outcomes were collected. Multidrug resistance was defined as acquired non-susceptibility to at least 1 agent in 3 or more antibiotic classes. In total, 64 (53.7%) patients developed 96 episodes of culture-proven bacterial infection with 93 GNB isolates. Moreover, there were 58 (62.4%) MDR-GNB isolates, with a predominance of Klebsiella pneumoniae (32.7%), Escherichia coli (31%), and Pseudomonas aeruginosa (10.3%). Interestingly, 10 (17.2%) isolates were determined to be carbapenem-resistant Enterobacteriaceae . The median time to MDR-GNB infection was 9 (interquartile range: 5–33) days. The most common type of infection was intra-abdominal infection (47.9%). In the multivariate analysis, the significant variables associated with post-LT MDR-GNB infection include exposure to third-generation cephalosporins (hazard ratio [HR]: 2.16, P  = .023), operative time (hazard ratio [HR] 1.20, P  = .009), and length of intensive care unit stay (HR 1.03, P  = .049). With a focus on carbapenem-resistant Enterobacteriaceae infection, a pediatric end-stage liver disease score >21 was the only significant 6 variable in the multivariate analysis (HR 11.48, P  = .024). The overall 3-month mortality rate was 6.8%. This study has highlighted the high prevalence rate of MDR-GNB infection after pediatric LT. Therefore, caution on the emergence of MDR-GNB infection should be paid in at-risk children. Moreover, knowledge regarding the prevalence of MDR-GNB infection and resistant patterns is essential for guideline development to prevent and minimize the risk of MDR-GNB infection in this group of patients. Abstract : Supplemental Digital Content is available in the text